The Index of Microcirculatory Resistance as a Predictor of Echocardiographic Left Ventricular Performance Recovery in Patients With ST-Elevation Acute Myocardial Infarction Undergoing Successful Primary Angioplasty. - Faustino, M (2017)
BACKGROUND: This study aims to evaluate the relationship between IMR (Index of Microcirculatory Resistance) and the echocardiographic evolution of left ventricular (LV) systolic and diastolic performance after ST-elevation acute myocardial infarction (STEMI), undergoing primary angioplasty (P-PCI). METHODS: IMR was evaluated immediately after P-PCI. Echocardiograms were performed within the first 24 hours (Echo1) and at 3 months (Echo2): LV volumes, ejection fraction (LVEF), wall motion score index (WMSI), E/é ratio, global longitudinal strain (GLS), and left atrial volume were measured. RESULTS: Forty STEMI patients were divided in 2 groups according to median IMR: Group 1 (IMR < 26), with less microvascular dysfunction, and Group 2 (IMR > = 26), with more microvascular dysfunction. In Echo1 GLS was significantly better in Group 1 (-14.9 vs. -12.9 in Group 2, P = 0.005). However, there were no significant differences between the two groups in LV systolic volume, LVEF and WMS. Between Echo1 and Echo2, there were significant improvements in LVEF (0.48 ± 0.06 vs. 0.55 ± 0.06, P < 0.0001), GLS (-14.9 ± 1.3 vs. -17.3 ± 7.6, P = 0.001), and E/é ratio (9.3 ± 3.4 vs. 8.2 ± 2.0, P = 0.037) in Group 1, but not in Group 2: LVEF (0.49 ± 0.06 vs. 0.50 ± 0.05, P = 0.47), GLS (-12.9 ± 2.4 vs. -14.4 ± 3.2, P = 0.052), and E/é ratio (8.8 ± 2.4 vs. 10.0 ± 4.7, P = 0.18). WMSI improved significantly more in Group 1 (reduction of -17.1% vs. -6.8% in Group 2, P = 0.015). CONCLUSION: Lower IMR was associated with better myocardial GLS acutely after STEMI, and with a significantly higher recovery of the LVEF, WMSI, E/E' ratio and GLS, suggesting that IMR is an early marker of cardiac recovery, after acute myocardial infarction.